VD_FINDINFO Pron / 2014 / 25 vom 6. März 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN | 105 al. 1 CPC (CH), 105 al. 2 CPC (CH), 109 al. 1 CPC (CH), 241 CPC (CH)